2010
DOI: 10.2166/wst.2010.129
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical degradation of PAH compounds in process water: a kinetic study on model solutions and a proof of concept study on runoff water from harbour sediment purification

Abstract: The present study has investigated the possibility to apply electrochemical oxidation in the treatment of polycyclic aromatic hydrocarbon (PAHs) pollutants in water. The reaction kinetics of naphthalene, fluoranthene, and pyrene oxidation have been studied in a batch recirculation experimental setup applying a commercial one-compartment cell of tubular design with Ti/Pt(90)-Ir(10) anode. The rate of oxidation has been evaluated upon variations in current density, electrolyte composition and concentration. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 13 publications
(16 reference statements)
2
12
0
2
Order By: Relevance
“…) were in the same order of magnitude as degradation rates of other aromatic organics reported in the literature [8,15] and as the oxidation rates of the PAHs fluoranthene and pyrene obtained in the same setup at comparable current densities [26]. This showed that the initial oxidation of aromatic organics by the applied anode material was predominantly independent on the chemical nature of the molecules.…”
Section: Rno Absorbance Versus Ph By Chemical Adjustmentsupporting
confidence: 83%
“…) were in the same order of magnitude as degradation rates of other aromatic organics reported in the literature [8,15] and as the oxidation rates of the PAHs fluoranthene and pyrene obtained in the same setup at comparable current densities [26]. This showed that the initial oxidation of aromatic organics by the applied anode material was predominantly independent on the chemical nature of the molecules.…”
Section: Rno Absorbance Versus Ph By Chemical Adjustmentsupporting
confidence: 83%
“…6a and b). This supports prior findings [27], where the applied current density of 25 mA cm −2 was found as the most efficient setting during galvanostatic electrolysis of a similar PAH solution.…”
Section: Fate Of Halogenated Pahs During Eosupporting
confidence: 91%
“…PAHs as naphthalene, fluoranthene, and pyrene have in prior research been showed to be readily oxidized through EO in chloride electrolyte [27]. However, when increasing concentrations of sodium hypochlorite were added to batches of 0.10 M NaCl and PAH solutions no significant removal was observed (Fig.…”
Section: Identification Of Chlorinated Pahsmentioning
confidence: 88%
“…Using the water purification techniques and with suitable production we can eliminate these problems (11,13).…”
Section: Discussionmentioning
confidence: 99%
“…Within this method, Salmonella did not exist any longer after being washed by the neutral anolyte. Washing and sterilizing the meat processing instruments by neutral anolyte has many advantages in comparison with other approaches (10,11).…”
Section: Contextmentioning
confidence: 99%